Optimizing Antioxidant and Anti-Hyaluronidase Activities of Mixed Coffea arabica, Centella asiatica, and Curcuma longa Extracts for Cosmetic Application - Natthanan Phupaisan; Chadarat Ampasavate; Surapol Natakankitkul; Kanokwan Kiattisin (Cosmetics)
Coffea arabica, Centella asiatica, and Curcuma longa extracts have demonstrated significant antioxidant and anti-aging activities. However, research on combining these three extracts in specific proportions to enhance their antioxidant and anti-hyaluronidase effects remains limited. Therefore, this study aimed to determine the optimal proportions of C. arabica, C. asiatica, and C. longa extracts to maximize their combined antioxidant and anti-hyaluronidase activities. A two-level full factorial design was used to identify the optimal concentration ratios of the mixed extracts. The results indicated that all extracts influenced antioxidant activity, with the optimal proportions of C. arabica, C. asiatica, and C. longa extracts being 0.5:6:2 mg/mL, respectively. In addition, all factors affected hyaluronidase enzyme inhibition, with the optimal proportions for C. arabica, C. asiatica, and C. longa extracts being 10:10:5 mg/mL to achieve the best inhibition. In a photostability study on individual extracts, mixed extracts, and mixed extracts combined with sodium metabisulfite and bis-ethylhexyloxyphenol methoxyphenyl triazine, it was observed that preparing the mixed extracts and adding an antioxidant and a sunscreen agent helped reduce the photodegradation of phenolic compounds in the mixed extracts. Consequently, the stabilized mixed extracts could serve as raw materials in cosmetic products.